Interplay of Liver–Heart Inflammatory Axis and Cannabinoid 2 Receptor Signaling in an Experimental Model of Hepatic Cardiomyopathy. Issue 4 (24th January 2020) - Matyas, Csaba; Erdelyi, Katalin; Trojnar, Eszter; Zhao, Suxian; Varga, Zoltan V.; Paloczi, Janos; Mukhopadhyay, Partha; Nemeth, Balazs T.; Haskó, György; Cinar, Resat; Rodrigues, Robim M.; Ait Ahmed, Yeni; et al.
Abstract : Background and Aims: Hepatic cardiomyopathy, a special type of heart failure, develops in up to 50% of patients with cirrhosis and is a major determinant of survival. However, there is no reliable model of hepatic cardiomyopathy in mice. We aimed to characterize the detailed hemodynamics of mice with bile duct ligation (BDL)–induced liver fibrosis, by monitoring echocardiography and intracardiac pressure–volume relationships and myocardial structural alterations. Treatment of mice with a selective cannabinoid‐2 receptor (CB2 ‐R) agonist, known to attenuate inflammation and fibrosis, was used to explore the impact of liver inflammation and fibrosis on cardiac function. Approach and Results: BDL induced massive inflammation (increased leukocyte infiltration, inflammatory cytokines, and chemokines), oxidative stress, microvascular dysfunction, and fibrosis in the liver. These pathological changes were accompanied by impaired diastolic, systolic, and macrovascular functions; cardiac inflammation (increased macrophage inflammatory protein 1, interleukin‐1, P‐selectin, cluster of differentiation 45–positive cells); and oxidative stress (increased malondialdehyde, 3‐nitrotyrosine, and nicotinamide adenine dinucleotide phosphate oxidases). CB2 ‐R up‐regulation was observed in both livers and hearts of mice exposed to BDL. CB2 ‐R activation markedly improved hepatic inflammation, impaired microcirculation, and fibrosis. CB2 ‐R activation also decreased serum tumor necrosis factor‐alpha levels and improved cardiac dysfunction, myocardial inflammation, and oxidative stress, underlining the importance of inflammatory mediators in the pathology of hepatic cardiomyopathy. Conclusions: We propose BDL‐induced cardiomyopathy in mice as a model for hepatic/cirrhotic cardiomyopathy. This cardiomyopathy, similar to cirrhotic cardiomyopathy in humans, is characterized by systemic hypotension and impaired macrovascular and microvascular function accompanied by both systolic and diastolic dysfunction. Our results indicate that the liver–heart inflammatory axis has a pivotal pathophysiological role in the development of hepatic cardiomyopathy. Thus, controlling liver and/or myocardial inflammation (e.g., with selective CB2 ‐R agonists) may delay or prevent the development of cardiomyopathy in severe liver disease.